Effects of different grain types on nutrient apparent digestibility, glycemic responses, and fecal VFA content in weaned foals - Xinxin Huang; Qian Li; Xuanyue Li; Chao Li; Jiahao Li; Linjiao He; Hongxin Jing; Fan Yang; Xiaobin Li (BMC Veterinary Research)
Abstract Background China's equine industry has shifted from traditional rough grazing to modern intensive farming, expanding the roles of horses into eventing, leisure, tourism, and meat and dairy production. Concurrently, equine nutrition has evolved from a forage-based diet to a more diverse regimen incorporating grain supplements to meet the heightened energy demands of intensive farming. However, nutrient digestibility and glycemic response vary considerably based on grain type, starch content, composition, and structural properties. Optimal grain selection is therefore essential for energy supplementation across developmental stages to sustain growth and performance. This study examines the impact of diets incorporating steam-flaked grains (corn, oats, and barley) on apparent nutrient digestibility, glycemic response, and fecal volatile fatty acid (VFA) composition in the weaned Kazakh foals. Methods Eighteen male Kazakh foals, weaned at 5 months, were randomly assigned to three groups (n = 6 per group) based on grain type: corn group (CG), oats group (OG), and barley group (BG). The daily starch intake for the foals was set at 2 g starch (DM)/kg body weight per day to determine the amount of concentrate supplements to be fed, based on the principle of equal grain starch intake over a 60-day feeding trial. Results Results indicated that the apparent nutrient digestibility was lower in OG than in CG and BG (P > 0.05). However, amylose intake and digestibility were significantly higher in OG compared to CG (P < 0.01). Plasma glucose and glucagon levels were elevated in CG relative to OG and BG (P < 0.01), while the insulin/glucose ratio was highest in the BG. Additionally, BG increased fecal lactic acid and total VFA (TVFA) concentrations while reducing fecal pH. Conclusions For weaned Kazakh foals, steam-flaked corn could be recommended in advance of steam-flaked oats and barley in cereal-based energy supplementation alongside basal forage diets. It may reduce amylose intake, improve glycemic responses, increase plasma glucose levels and reduce fecal lactic acid content.